Animal welfare in Animal Bioclimatology classes - Ramalho de Lima, Matheus (Spei Domus, 2015)
Purpose: the purpose of this review is to address issues related to the teaching of Animal Welfare (bea), focusing on the Brazilian case, and discuss the challenges and possibilities for improvement. Description: it is essential that students of animal science courses in the undergraduate program learn the conceptual foundations and main applications of bea. Point of view: while bea teaching in Brazilian universities has had a marked growth in recent years and has allowed to identify some of its national characteristics, it in turn benefits significantly from the association with research as this is an area of knowledge under construction. Conclusions: the main challenges posed in terms of bea teaching in Brazil are discussed. By introducing bea teaching into their curricula, universities increase its graduates’ suitability for current labor market and contribute to progress in the ethics of human-animal relationship.